Measurement model of professor professional work - L. . Letova (Высшее образование в России)
The article shows the advantages of the Rush model as a methodological tool formeasurement of latent variables in social sphere. The OmSTU experience in using the model to measure the latent value «professional work of a professor» is summarized.